AMPERE (Asset Mapping Platform for Emerging CountRies Electrification) a GNSS-based integrated platform for energy decision makers - Marco Nisi (mediaGEO soc. coop., 2021)
The purpose of the AMPERE (Asset Mapping Platform for Emerging countRies Electrification) project is to provide a dedicated solution for electrical power network information gathering: AMPERE will support decision making actors (e.g. institutions and public/ private companies in charge to manage electrical network) to collect all needed info to plan electrical network maintenance and upgrade. AMPERE solution is based on a GIS Cloud mapping technology, collecting on field data acquired with optical/thermal cameras and LIDAR installed on board a Remote Piloted Aircraft (RPA). AMPERE project has received funding from the European GNSS Agency (grant agreement No 870227) under the European Union's Horizon 2020 research and innovation programme.